Spirituelle revolutioner - Afropæiske kropspolitikker og kunstens ’sekularisering’ - Lockward, Alanna (K&K - Kultur og Klasse, 2015)
A Vodoun ceremony heralded the beginning of the end of Europe’s savage capitalist enterprise in the Caribbean and elsewhere. According to Laurent Dubois we are all descendants of the Haitian Revolution and therefore accountable to its ancestry. In my presentation I will discuss how the liberation Pan-Africanist legacies of the maroon leaders that created the first Black Republic is present in some Afropean Decolonial Aesthetics/Aesthesis practitioners, such as Teresa María Díaz Nerio, Jeannette Ehlers, Quinsy Gario and Patricia Kaersenhout, as well as in other Caribbean (Diaspora) artists. Apart from the paradigmatic work of Renée Cox honouring the legacy of the Jamaican heroine Queen Nanny of the Maroons, who was their armed and spiritual leader, there is as well the radical legacy of Ana Mendieta who combined in her work some of the basic premises of maroon life, namely a permanent dialogue with nature and its spirits. Nicolás Dumit Estévez and Charo Oquet, for example, resonate with the spiritual legacies of marronage, consistently contributing to dismantle one of the most successful fallacies of modernity: the so-called ‘secularity’ of the arts. Furthermore, Miami-based Adler Guerrier revisits Charles Mingus’ Haitian Fight Song in a film where his interpretation of the flâneur defies the painful erasure by colonial archives on the African continent and elsewhere on Black radical legacies. This particular type of awareness of a urban landscape as a space where the mere presence of a Black body represents both a transgression and an affirmation of being is reminiscent of the armed struggle spirit of those runaway warriors. In this sense, these artists are expanding the stamina of Decolonial Aesthetics/Aesthesis by focusing their attention on the forms of sensing and inhabiting the world that the modern/colonial order has suppressed.